DRYING KINETICS OF OIL PALM FROND WASTE USING SIMPLE BATCH OVEN DRYER (Universitas Negeri Semarang, 2016)
Drying phenomena of oil palm frond waste as agriculture waste was observed using simple batch oven dryer. The operation temperatures were 50, 80 and 120 °C. The sample of oil palm frond was weighed periodically every 30 minutes. Moisture content, shrinkage phenomena and drying kinetic model were investigated to the difference operation temperature. Experimental result exhibited that temperature influent significantly to the drying rate. The water transport controlled by diffuse mechanism. Shrinkage occurred in radial direction and decreased the size to almost 65% from initial size. In longitudinal direction almost is not change of size.